Optimalisasi Peran Masjid Baitussalam Sebagai Pusat Pendidikan Nonformal dan Pemberdayaan Masyarakat - Kurniari, Akhmad; Ananda P, Deanira; Resati, Hanifa Tun; Fauziyyah, Ghina; Yusuf, Reza; Sahal, Muhammad Sofwan; Fauziah, Kholifatul (Universitas Muhammadiyah Yogyakarta, 2025)
The preliminary study through observation shows that the TPA has a limited number of teachers, so TPA cannot be done regularly or only when there are teachers. In addition, in the mosque area there is an empty cupboard that has the potential to be utilized as a reading corner to increase the interest in reading of the congregation. This Student Service Program aims to (1) strengthen the role of the Baitussalam Mosque as a non-formal education center through improving the quality of teaching at the Al-Qur'an Education Park (TPA), (2) provide more adequate literacy facilities through the procurement and management of reading corners, (3) beautify the mosque environment to welcome the holy month of Ramadan. This program coincides with the month of Sha'ban which indicates the presence of Ramadan in the near future. This program was implemented through several stages, namely preparation, implementation, and monitoring and evaluation. The results of this program are an increase in the number of TPA teachers from the comunity service team so that TPA can be routinely carried out, the availability of a reading corner containing a collection of Islamic books and children's reading, and a tidier and more beautiful mosque in welcoming the month of Ramadan. In addition, the cleanliness of the mosque increased significantly, creating a more comfortable worship environment for worshipers.